A Comparison Analysis between a Fixed and Multi-Step Size MPPTs for PV System under Variable Irradiance and Real Solar Curve - Y. AMARA (International Journal of Engineering and Management Research, 2022)
The control of the power electronic interfaces is essential to ensure the high efficiency of the photovoltaic system. In a DC stand-alone photovoltaic system, the boost converter is the most used. A regulator named maximum Power Point Tracking (MPPT) is inserted to control the ON/OFF states. Incremental conductance (In-Cond) is widely used to extract the maximum power point (MPP) from the Photovoltaic panel. It presents more efficiency and reliability compared to the conventional perturb and observes (P&O) technique. However, it presents power loss during the variations appearing during changes in weather conditions, due to the use of fixed step size. Accordingly, the present paper proposes a Multi-step size In-Cond to adapt the PV system to any change of the applied irradiance and to overcome the drawbacks of the existing In-Cond. Indeed, the present contributions introduced two-steps sizes instead of one. The principle is to design a step size value when approaching the MPP and a large value when the operating point is far from the MPP. Simulations and comparisons through MATLAB/Simulink under various applied conditions show that the proposed technique outperforms the conventional Inc-Cond in terms of convergence speed, response time, stability, and performance.